2014
DOI: 10.2174/1389557514666140123124321
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Phytotherapeutic Approaches for the Treatment of Benign Prostatic Hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is the noncancerous growth of the prostate gland resulting due to overproliferation of the stromal and glandular elements of the prostate and is associated with lower urinary tract symptoms. Natural products, containing inherently vast structural diversity than synthetic compounds, have been the major resources of bioactive agents and will continue to play as protagonists for discovering new drugs. Phytotherapeutic products have been used traditionally in developing countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Investigating of uncomplicated lower urinary tract symptoms (LUTS) in men who used a self-management programme in addition to standard care or standard care alone demonstrated that behavioural treatment reduced nightly nocturia by a mean of 0.97 episodes and was significantly more effective than drug therapy (5) . However, all attention in alternative approach for BPH was usually associated with the phytotherapeutic agents, as natural products, containing inherently vast structural diversity than synthetic compounds, have been the major resources for discovering new drugs (6) . For the purpose of a targeted conservative treatment for men with BPH Dr Allen suggested Thermobalancing therapy enabled by topically applied therapeutic device to the projection of prostate (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Investigating of uncomplicated lower urinary tract symptoms (LUTS) in men who used a self-management programme in addition to standard care or standard care alone demonstrated that behavioural treatment reduced nightly nocturia by a mean of 0.97 episodes and was significantly more effective than drug therapy (5) . However, all attention in alternative approach for BPH was usually associated with the phytotherapeutic agents, as natural products, containing inherently vast structural diversity than synthetic compounds, have been the major resources for discovering new drugs (6) . For the purpose of a targeted conservative treatment for men with BPH Dr Allen suggested Thermobalancing therapy enabled by topically applied therapeutic device to the projection of prostate (7) .…”
Section: Introductionmentioning
confidence: 99%
“…However, 5α-reductase inhibitors may have serious side-effects, such as orthostatic hypotension, decreased libido and ejaculation, or erectile dysfunction [ 6 ]. Owing to the small number of adverse effects of natural products, they have been considered as alternative treatments for BPH [ 7 ].…”
mentioning
confidence: 99%